Factors associated with online information seeking about mental health among high school students in Belgrade, Serbia - Tatjana Gazibara; Jelena Cakic; Milica Cakic; Anita Grgurevic; Tatjana Pekmezovic (Cambridge Prisms: Global Mental Health)
Adolescents may not necessarily have a specific mental health challenge to seek information on mental health. They may be genuinely curious on how to better understand these issues, especially when mental health is being discussed in school, among peers and with parents. The purpose of this study was to examine the frequency and factors associated with online information seeking about mental health among adolescents. A total of 702 high school students from Belgrade, Serbia, participated in the study and filled in an anonymous questionnaire about sociodemographics, digital behaviors and the Electronic Health Literacy Scale (eHEALS). The prevalence of seeking information about mental health in our study sample was 23.5% (165/702). The multivariate model showed that having a lower school performance, lower eHEALS score and browsing health blogs, social media and websites run by physicians and health institutions were independently associated with online information seeking about mental health. Additionally, searching for online information about psychoactive substances, bullying and medications was independently associated with online information seeking about mental health among adolescents. Adolescents are familiar with a variety of sources of online health information, but choose specific online platforms to read about mental health. These platforms could be utilized to promote mental well-being in high schools.